Histrionic personality disorder: Definition, clinical profiles, differential diagnosis and therapeutic framework - Perrotta, Giulio (Archives of Community Medicine and Public Health, 2021)
Starting from the general concept of “histrionic personality”, the present work focuses on the essential aspects of personality disorder that defi ne the clinical and diagnostic contexts, laying the foundations for a correct differential diagnosis, without neglecting the neural characteristics developed by the scientific community. The discussion ends with the best suggested therapeutic approaches.